The ‘cupola’ of the Ṣanʿāʾ cathedral: it still exists - Daum, Werner (Proceedings of the Seminar for Arabian Studies, 2025)
Abraha’s cathedral in Ṣanʿāʾ was the predecessor of the Great Mosque. When the church was demolished in the mid-eighth century AD, much of its material (columns, capitals, beams, painted ceilings) was reused for the mosque. These elements have been known and recognized for quite a while. To them, we must now add a recent discovery: the alabaster ‘cupola’, which al‑Azraqī describes as the great wonder of the church. However, for technical and Byzantine architectural and historical reasons, the church’s qubbah cannot have been ‘one’ cupola. Only an ensemble of small dome-like skylights inset with alabaster plaques is imaginable. From the point of view of style and size, these are clearly the five small domes near the Great Mosque’s mihrab. The mosque’s recent restoration by the Istituto Veneto per i Beni Culturali has exposed the alabaster plaques of these cupolas; they can be dated to the sixth century AD. They are not just another element of spolia from the church but had been what could be termed its spiritual heart, transposed with the same meaning.